2007
DOI: 10.1159/000110009
|View full text |Cite
|
Sign up to set email alerts
|

Nanoparticle-Based Oral Drug Delivery System for an Injectable Antibiotic – Streptomycin

Abstract: Background: To develop an oral drug delivery system for an injectable antibiotic, streptomycin. Methods: Poly-lactide-co-glycolide (PLG) nanoparticles encapsulating streptomycin were prepared by the multiple emulsion technique and administered orally to mice for biodistribution and chemotherapeutic studies. Results: The mean particle size was 153.12 nm with 32.12 ± 4.08% drug encapsulation and 14.28 ± 2.83% drug loading. Streptomycin levels were maintained for 4 days in the plasma and for 7 days in the organs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(23 citation statements)
references
References 33 publications
0
23
0
Order By: Relevance
“…Pandey and Khuller [89] designed nanoparticle for the growth of oral drug delivery system, and recommended that nano-encapsulation may be useful for developing an appropriate oral dosage form for streptomycin, and for other antibiotics that are, if not injectable [89]. Elechiguerra et al [90] demonstrated the interaction of metal nanoparticles with viruses and explained that silver nanoparticles experience a size-dependent interaction with HIV-1; the nanoparticles of 1-10 nm close to the virus.…”
Section: Metal Solutionmentioning
confidence: 99%
“…Pandey and Khuller [89] designed nanoparticle for the growth of oral drug delivery system, and recommended that nano-encapsulation may be useful for developing an appropriate oral dosage form for streptomycin, and for other antibiotics that are, if not injectable [89]. Elechiguerra et al [90] demonstrated the interaction of metal nanoparticles with viruses and explained that silver nanoparticles experience a size-dependent interaction with HIV-1; the nanoparticles of 1-10 nm close to the virus.…”
Section: Metal Solutionmentioning
confidence: 99%
“…A number of other promising nanoformulation approaches are also available for this purpose (Pandey et al 2003;Zahoor et al 2005), whereas other groups have instead used subcutaneous or intravenous liposomal or niosomal formulations to target the pulmonary compartment (Adams et al 1999;El-Ridy et al 2007). Alternatively, using nanodispersion or nanoparticle techniques it may be possible to obtain oral formulations of drugs previously only delivered by injection (Pandey and Khuller 2007). Although much work remains to be performed in this area, these technologies have considerable potential to overcome some of the current limitations of drug delivery in tuberculosis.…”
Section: Pharmacological Considerations In Tuberculosismentioning
confidence: 99%
“…For example, PLGA nanoparticles can generally resist the environment of the gastrointestinal tract when administered orally (Li et al, 2008;Pandey & Khuller 2007;Shaikh et al, 2009). Nevertheless, to increase the stability in acid environments a strategy has been developed of polyethylene glycol coating (PEG, Garinot et al, 2007) that decreases interaction with the environment and offers protection from the medium and macrophages (Owens & Peppas 2006).…”
Section: Poly (Dl-lactic-co-glycolic) Acid (Plga)mentioning
confidence: 99%